Cross-Clade Recognition of HIV-1 CAp24 by CD4(+) T Cells in HIV-1-Infected Individuals in Burkina Faso and Germany - Böhler, Thomas (Bentham Open, 2009)
The presence of antigen-specific cellular immune responses may be an indicator of long-term asymptomatic HIV-1-disease. The detection of cellular immune responses to infection with different subtypes of HIV-1 may be hampered by genetic differences of immunodominant antigens such as the capsid protein CAp24. In Nouna, Burkina Faso, HIV-1 circulating recombinant forms CRF02_AG and CRF06_cpx are the 2 major strains detectable in HIV-1-infected individuals, while subtype B strains prevail in Europe and North America. Amino acid sequences of CAp24 were assessed in blood samples from 10 HIV-1-infected patients in Nouna, Burkina Faso. Production of interferon-gamma (IFN-γ) in peripheral blood CD4(+) lymphocytes in response to recombinant HIV-1 proteins derived from clade B (including CAp24(NL4-3)) was measured using a modified flow-cytometry-based whole blood short term activation assay (FASTimmune, BDBiosciences). IFN-γ production following stimulation with a whole length CAp24 protein derived from clade B (CAp24(NL4-3)) was additionally quantified in comparison to a CAp24 protein derived from CRF02_AG (CAp24(BD6-15)) in 16 HIV-1-infected patients in Heidelberg, Germany. Amino acid sequence identity of CAp24 obtained from patients in Nouna ranged between 86 and 89% when compared to the clade B CAp24(NL4-3) consensus sequence, between 90 and 95% when compared to the circulating recombinant form CRF06_CPX consensus sequence, and between 92 and 96% when compared to the CAp24(BD6-15) consensus sequence. Significant numbers of HIV-1-specific CD4(+) lymphocytes producing IFN-γ were detected in 4 of 10 HIV-1-infected patients. In 7 of 16 patients in Heidelberg, recombinant CAp24(BD6-15) stimulated IFN-γ-production in CD4(+) lymphocytes to a similar extent as the clade B-derived CAp24(NL4-3). Thus, antigen-specific CD4(+) lymphocytes from both West African and European patients infected with different strains of HIV-1 show relevant cross-clade recognition of HIV-1 CAp24 in a flow-cytometry-based whole blood short term activation assay.